2020
DOI: 10.1049/iet-ipr.2019.1526
|View full text |Cite
|
Sign up to set email alerts
|

Unified deep learning approach for prediction of Parkinson's disease

Abstract: The paper presents a novel approach, based on deep learning, for diagnosis of Parkinson's disease through medical imaging. The approach includes analysis and use of the knowledge extracted by Deep Convolutional and Recurrent Neural Networks (DNNs) when trained with medical images, such as Magnetic Resonance Images and DaTscans. Internal representations of the trained DNNs constitute the extracted knowledge which is used in a transfer learning and domain adaptation manner, so as to create a unified framework fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…The results of the study showed how prediction accuracy of UPDRS increases as DL is aided by cluster analysis. A DL approach by combining CNN and RNN was investigated in [162] and a high prediction accuracy was obtained to classify PD from non-PD. A homeenvironment friendly IMU sensor based system for detecting freezing of gait was investigated in [163].…”
Section: ) Ml-based Approaches In Pd Diagnosismentioning
confidence: 99%
“…The results of the study showed how prediction accuracy of UPDRS increases as DL is aided by cluster analysis. A DL approach by combining CNN and RNN was investigated in [162] and a high prediction accuracy was obtained to classify PD from non-PD. A homeenvironment friendly IMU sensor based system for detecting freezing of gait was investigated in [163].…”
Section: ) Ml-based Approaches In Pd Diagnosismentioning
confidence: 99%
“…Recent research has focused on extracting trained DNN representations and using them for classification purposes [4], either by an auto-encoder methodology, or by monitoring neuron outputs in the convolutional or/and fully connected network layers [15,34]. Such developments are exploited in this paper, combined with clustering, for diagnosis of diseases based on medical imaging.…”
Section: Related Workmentioning
confidence: 99%
“…The extracted features are used to construct a deep learning model, which is very likely to accelerate the convergence speed of model training, reduce the demand for training data, and improve model performance ( Liu et al, 2018 ). On the other hand, the large data training samples required for deep learning and the large number of parameters required for model adjustment can easily lead to a much higher computational complexity and the amount of data required for training models than traditional machine learning models ( Jha and Kwon, 2017 ; Huang et al, 2020 ; Wingate et al, 2020 ). Therefore, although current neuroimaging databases have been well developed, their scale may limit the performance of deep learning to a certain extent.…”
Section: Related Workmentioning
confidence: 99%